2015
DOI: 10.3174/ajnr.a4392
|View full text |Cite
|
Sign up to set email alerts
|

pCONus Device for the Endovascular Treatment of Wide-Neck Middle Cerebral Artery Aneurysms

Abstract: BACKGROUND AND PURPOSE: Endovascular treatment of bifurcation middle cerebral artery aneurysms with a wide neck could be challenging, and many lesions are still treated by a surgical approach. The pCONus is a newly emerging device for wide-neck bifurcation intracranial aneurysms. To date, a single report on the treatment of intracranial aneurysms including all locations has been published. We report our experience with pCONus in the treatment of wide-neck MCA aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…Four of the aneurysms in our series were included in a multicenter analysis of 40 middle cerebral artery aneurysms treated with the pCONus device 24. The initial angiographic results were in line with our results and those of Aguilar Pérez et al , with a complete occlusion rate of 25% and a neck remnant in 47.5%.…”
Section: Discussionsupporting
confidence: 88%
“…Four of the aneurysms in our series were included in a multicenter analysis of 40 middle cerebral artery aneurysms treated with the pCONus device 24. The initial angiographic results were in line with our results and those of Aguilar Pérez et al , with a complete occlusion rate of 25% and a neck remnant in 47.5%.…”
Section: Discussionsupporting
confidence: 88%
“…Immediate angiogram results showed complete occlusion in one patient and 5 small aneurysm and neck remnants. In line with other studies, the overall performance of the device has so far produced satisfactory clinical results [23][24][25][26][27]. There were no significant clinical complications associated with the use of the device and all patients were discharged with no permanent neurological deficits.…”
Section: Discussionsupporting
confidence: 63%
“…There are several studies that have assessed the effectiveness of the pCONus device in unruptured aneurysms but only one currently published study on its use in ruptured aneurysms [23][24][25][26]. Aguilar-Perez et al, 2016, has shown encouraging results in 21 patients with ruptured aneurysms that were treated with the pCONus device [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are several existing neck bridging devices, including the pCONus1, PulseRider ® , and the eCLIPs™. Numerous case series have been published detailing the use of the pCONus1 in both ruptured and unruptured aneurysms as well as in conjunction with other devices [12][13][14][15][16]. Gory et al [17] recently published their 1-year results on the use of the pCONus1 in wide-necked middle cerebral artery aneurysms.…”
Section: Discussionmentioning
confidence: 99%